PENGARUH MEDIA ADOBE ILLUSTRATOR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA SRIJAYA NEGARA - Fifi Novitasari; Yulia Djahir; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aims to determine the effect of the Adobe Illustrator media on the learning outcomes among the students in economic subjects at SMA Srijaya Negara Palembang. It concerns with a type of experiment called “Experimental”, taking the form of “pre- Experimental Designs” along with “One-group pretest-posttest”. The entire class X IIS population which consists of 4 classes of totalling as many as 141 students. The sample of this reasearch uses the Random Sampling so that it obtains one class, namely; class X IIS 2 of 26 students as the experimental class treated by using the Adobe Illustrator media. The tecnique of data collection is obtained by using tests and observation. The data analysis technique used to test the hypothesis Product Moment of 0.9453, influencing on students’ learning outcomes, and test t calculated of 86.92 ttable ≥ 1.711. If tcounted ≥ ttable then Ho is rejected and Ha accepted. The test-results of hypotheses can be concluded that there is influence of Adobe Illustrator media on learning outcomes of students in economics subjects at SMA of Srijaya Negara, Palembang.